Coupling Gastro-Intestinal Tract Analysis With an Airborne Contamination Control Method to Estimate Litter Ingestion in Demersal Elasmobranchs - Pedà, Cristina; Battaglia, Pietro; D’Alessandro, Michela; Laface, Federica; Malara, Danilo; Consoli, Pierpaolo; Vicchio, Teresa Manuela; Longo, Francesco; Andaloro, Franco; Baini, Matteo; Galli, Matteo; Bottari, Teresa; et al. (Frontiers in Environmental Science, 2020)
This study aims to assess the litter ingestion in some demersal elasmobranchs, combining a classical gastro-intestinal tract (GIT) analysis with a procedure methodology to reduce airborne fibres contamination. In order to prevent the overestimation of litter ingestion, we applied severe mitigation measures to avoid airborne contamination during the analyses, integrating a new approach for the correction of estimates of fibres abundance using control procedure. In this study, we assessed the anthropogenic litter ingestion in four elasmobranch species from the southern Tyrrhenian Sea: Scyliorhinus canicula (n= 27), Etmopterus spinax (n= 16), Galeus melastomus (n= 12) and Raja clavata (n= 6). The gastro-intestinal tract of each specimen was analysed by visual sorting and the polymers identified by FT-IR spectroscopy technique. Overall, 19 litter particles were found in the gastro-intestinal tract of 13 demersal elasmobranchs (%O= 21) and for the first time, evidence of litter ingestion by R. clavata in Mediterranean waters was also reported. In G. melastomus and R. clavata all anthropogenic particles were plastics, whereas in S. canicula other litter categories were also found. No litter ingestion was instead observed in E. spinax. More than 50% of litter particles belonged to microlitter category (< 5 mm). Polyamide was the only polymer typology found in all examined species. We described the procedures to control the airborne contamination applied at each step of laboratory analysis and, thanks to the application of our control method, it was possible to exclude the 95% of fibres found in samples from the assessment. Moreover, we compared fibres abundances observed in samples and controls. This study, combining an approach for minimizing the bias associated to airborne fibre contamination, provided a reliable assessment of marine litter ingestion in demersal elasmobranchs.